Pre-school teachers’ knowledge of early childhood assessment and domains of learning commonly assessed in Ondo West Local Government Area, Ondo State, Nigeria (2018)
Children have unique nature and characteristics. Because of this, regular and holistic assessment of their learning and development is necessary. This could be done through observation, administration of standardized and teacher-made assessment instrument and children work. For assessment of pre-school children to be done effectively, teachers at this level of education need to have good knowledge of what early childhood assessment is all about. This study, therefore, examined pre-school teachers’ knowledge of early childhood assessment and domains commonly assessed in early childhood education centres in Ondo West Local Government Area of Ondo State. The study adopted descriptive survey design. The sample for the study comprised one hundred preprimary school teachers selected from both public and private schools through the use of purposive sampling. "Test on Teachers’ Knowledge of Early Childhood Assessment” (r=0.79) and “Checklist on Domains Commonly Assessed by Pre-school Teachers” (r=0.80) were instruments used for the study. Data collected were analysed using percentage, mean and standard deviation. Findings from the study revealed that the pre- primary school teachers’ level of knowledge on early childhood assessment in Ondo West Local Government Area was low (x = 38.71; SD = 16.31). Cognitive domain was the one most commonly assessed by the pre-primary school teachers (x = 3.40); with less emphasis on the assessment of other developmental domains which are the physical (x=1.58), social (x=1.60) and emotional (x=1.46). The implication is that, since the pre-schoolers are not properly assessed in all the domains of development through the use of appropriate assessment tools, they will not have the advantage of experiencing holistic development. It was, therefore, recommended that Pre-service ECE teacher education programmes should be reviewed such that teachers-in-training can acquire appropriate knowledge and skills in ECE assessment. School heads and owners should alsoorganize in-service training, seminars and workshops on assessment in early childhood education periodically so as to train and expose the pre-primary school teachers to contemporary assessment practices in early childhood education.